PERGERAKAN JARINGAN ISLAM LIBERAL (JIL) DI INDONESIA TAHUN 2001-2005 - Tri Agustina, Cahyaningrum (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret)
This article aim to explain some light on liberal Islamic movements in Indonesia, with specific reference to the Liberal Islam Network (JIL). The background formation of Liberal Islam Network is the strengthening influence of orientalists in Islamic studies and the rise of fundamentalist Islamic groups that tend to be radical in overcome the problem post new order. Liberal Islam Network which initiated Ulil Abshar Abdalla and active on March 8, 2001. Liberal Islamic thought are reflected in several important agenda of JIL, which include: the political agenda (secularism), religious pluralism, emancipation of women, freedom of opinion and freedom of expression. Liberal Islamic thought development strategies implemented with financial assistance of The Asia Foundation through study and discussion forums, print media such as Gatra, Tempo, Jawa Pos to electronic media (radio news agency 68H) and internet with the official website www.islamlib.com. The effect of Liberal Islam Network in Indonesia is a confirmation of theology the secular state idea and religious pluralism. The aims of Liberal Islam Network to promote the ideals of civil society (freedom of civil society), the development would have a response and critique of various parties.